Impact of the COVID-19 pandemic on general surgery residency program in Peru: A cross-sectional study - Huamanchumo-Suyon, Medalit E. (2020)
Background: General surgey is a specialty of high demand and relevance. We aimed to collect the opinions of the residents and their tutors and heads of department, regarding the impact that this COVID-19 pandemic is having - and will probably have - on the training of future general surgeons in Peru. Methods: We conducted a cross-sectional study in Lima, Peru. We surveyed residents of general surgery, as well as their tutors and heads of surgery departments from 14 Peruvian hospitals. Results: The impact of COVID-19 was considered severe in approximately 60% of first-year residents, 100% of second-year residents, 40% of third-year residents and about 80% of attending physicians. The 68.8% of the residents considered that the loss of surgical training opportunities during the pandemic would negatively affect their job performance. In addition, as of 03/16/2020, no residents had performed more than 25 elective surgeries, trauma surgeries or laparoscopic procedures. All the participants (including tutors and heads of departments) highlighted the need to extend the residency period. Conclusion: The COVID-19 pandemic has affected the training of the general surgery residents. Deficiencies need to be identified in order to evaluate extending the period of the medical residency program in Peru.